希土類元素(ジスプロシウム, ユーロピウム, イッテルビウム及びイットリウム)のラットにおける経口投与時の排泄について - 外海, 泰秀; 村上, 喜八郎; 金本, 正文; 中村, 優美子; 坪井, 尚弘; 伊藤, 誉志男; 津村(長谷川), ゆかり (衛生化学, 1991)
Metabolisms of chlorides of 4 kinds of rare earth elements, i.e. dysprosium chloride (DyCl_3), europium chloride (EuCl_3), ytterbium chloride (YbCl_3) and yttrium chloride (YCl_3), were investigated in rats administered orally by a single dose. Male rats of Wistar strain, weighing 160-210 g, were used in the experiments. The experiments were performed by use of 3-4 rats for each group. The rats were fasted overnight before the experiments. The rare earth solutions of low dose (100 mg/kg/5 ml as rare earth elements) or high dose (1 g/kg/5 ml as rare earth elements) were administered orally, and the excretion of the rare earth elements in the feces and urine and the distribution of the rare earth elements in the whole blood, liver, spleen, bone and kidney were investigated. The four kinds of rare earth elements i.e. Dy, Eu, Yb and Y in the feces, urine or various organs were measured by the wet digestion method by using HNO_3 followed by ICP-AES. In the rats administered low dose, 92.0-98.4% of the administered rare earth elements were excreted into the feces within 4 d after the administration ; Similarly, 93.9-98.4% of the administered rare earth elements were excreted into the feces within 7 d after the administration in the rats administered high dose. None of the rare earth elements were detected in the urine. None of the rare earth elements were detected in the whole blood, liver, kidney, bone and spleen in the rats administered high dose or low dose. Therefore, it was suggested that DyCl_3,EuCl_3,YbCl_3 and YCl_3 were scarcely absorbed from the gastrointestine and excreted into the feces within 7 d when administered orally by a single dose.